SPECIFIC DENTAL TREATMENT OF FEMALE PATIENTS WITH BACTERIAL VAGINOSIS - А. Shulzhenko; E. Krutikova; L. Ostrovska; T. Petrushanko (Український стоматологічний альманах, 2018)
Inflammatory and dystrophic inflammatory periodontal diseases are the syndrome manifestation of such common diseases as diabetes mellitus, hyper-and hypothyroidism, gastric and duodenal ulcers, coronary heart disease and a number of other somatic pathologies. At the same time a number of publications on the relationship between the state of parodontium and urogenital diseases are not sufficient to date.